A Novel Heterocyclic Compound CE-104 Enhances Spatial Working Memory in the Radial Arm Maze in Rats and Modulates the Dopaminergic System - Aher, Yogesh D.; Subramaniyan, Saraswathi; Shanmugasundaram, Bharanidharan; Sase, Ajinkya; Saroja, Sivaprakasam R.; Holy, Marion; Höger, Harald; Beryozkina, Tetyana; Sitte, Harald H.; Leban, Johann J.; Lubec, Gert (Frontiers in Behavioral Neuroscience, 2016)
Various psychostimulants targeting monoamine neurotransmitter transporters (MAT) have been shown to rescue cognition in patients with neurological disorders and improve cognitive abilities in healthy subjects at low doses. Here, we examined the effects upon cognition of a chemically synthetized novel MAT inhibiting compound 2-(benzhydrylsulfinylmethyl)-4-methylthiazole (named as CE-104). The efficacy of CE-104 in blocking MAT (DAT – dopamine transporter, SERT – serotonin transporter and NET – norepinephrine transporter) was determined using in vitro neurotransmitter uptake assay. The effect of the drug at low doses (1 and 10mg/kg) on spatial memory was studied in male rats in the radial arm maze (RAM). Furthermore, the dopamine receptor and transporter complex levels of frontal cortex (FC) tissue of trained and untrained animals treated either with the drug or vehicle were quantified on blue native PAGE (BN-PAGE). The drug inhibited dopamine (IC50: 27.88µM) and norepinephrine uptake (IC50: 160.40µM), but had a negligible effect on SERT. In the RAM, both drug-dose groups improved spatial working memory during the performance phase of RAM as compared to vehicle. BN-PAGE western blot quantification of dopamine receptor and transporter complexes revealed that D1, D2, D3 and DAT complexes were modulated due to training and by drug effects. The drug’s ability to block DAT and its influence on dopamine transporter and receptor complex levels in the FC is proposed as a possible mechanism for the observed learning and memory enhancement in the RAM.